Evaluation of underutilized fern Cyathea gigantea from Northeast India for its potentiality in food processing - Deepanka Saikia
Cyathea gigantea is a species of tree fern found in the North-Eastern part of India in Arunachal Pradesh. Pith of Cyathea gigantea fern is a useful but underutilized part, popularly known as tashe, has traditionally been consumed by the natives of Arunachal Pradesh. From time immemorial, tashe rich in carbohydrates has been consumed as a supplementary food by several tribes like Solungs, Nyishis, Tagins and Adis when faced under natural calamities like famine and earthquake. Tashe being an important source of healthy diet was studied to determine its physico-chemical characteristics to validate the traditional knowledge about its goodness in consumption. The physical and functional properties selected for evaluation were bulk density, colour and pasting properties and nutritional properties selected for evaluation were the content of moisture, ash, protein, fat, crude fibre, carbohydrate, energy value and antioxidant levels as per the standard procedure. From the study it has been found that moisture content in tashe flour is less offering a longer shelf life. The lower fat per cent of tashe makes it an ideal health food option, particularly for those who are overweight. Tashe flour has a low bulk density of less than 1 g/cm3, making it ideal for preparation of complementary foods. It has been concluded from the study that tashe flour can be used to replace traditional flours in a number of flour-based products due to its promising properties.